The role of law enforcement in helping and responding to individuals with mental illness: police and family perspectives - Hirschi, Melissa (2017)
Police and family members often serve as the first responders in times of crisis for individuals living with mental illness. Research that focuses on families examines the burden of caring for loved ones with mental illness (e.g., subjective burden such as emotional impact and objective burden such as physical or financial impact). Police responses to individuals with mental illness have been shown to focus primarily on post-contact decisions (e.g., arrest, diversion, use of force, and peace keeping) as well as implementation of policy responses (e.g., critical incident teams). This dissertation contributes to the existing literature by examining factors that impact police responses to individuals with mental illness, including the role of power, as seen from both the police and family perspectives. Utilizing the theoretical frameworks of collective consciousness, bureaucracy, and power, a more comprehensive understanding of police responses to mental health calls is gained. Using a phenomenological approach, semi-structured, in-depth interviews were conducted with police officers (n = 34) and family members of individuals living with mental illness (n=5). Creswell’s (2013) five steps to phenomenological data analysis were followed. NVivo data software was used to assist with coding and data management. The data from this study provide insight into the complex contextual landscape of police responses to individuals with mental illness. Such responses are influenced by personal, bureaucratic, community, and systemic factors. The family experience and perspective is also impacted by personal, community, and systemic influences. Data further revealed evidence of another dimension of power, a shift in responsibility for action (e.g., giving some measure of choice to another in the response or outcome). A new model detailing the complex landscape of police responses to individuals living with mental illness was developed and recommendations for appropriate forms of intervention were outlined. Building on and strengthening current models, opportunities for social work at this intersection are presented, including a focus on social justice and partnership with agencies and organizations